Comparison of medicinal plant knowledge between rural and urban people living in the Biosphere Reserve “Bioma PampaQuebradas del Norte”, Uruguay: an opportunity for biocultural conservation - Castiñeira Latorre, Elena (2018)
The Biosphere Reserve, UNESCO, “Bioma PampaQuebradas del Norte”, Rivera Department is an important reservoir of biocultural diversity of Uruguay. With the objective of contributing to its recognition and valuation, we describe the diversity of medicinal plants used by local communities in rural or urban settlements at the Reserve, from a qualiquantitative ethnobotanical approach. We estimated and compared species richness of alien and native medicinal plants mentioned by the 13 urban and 31 rural people in semistructured interviews selected by snowball sampling. We found that the diversity of medicinal plants comparing urban and rural areas did not present significant differences. However, rural areas report more native species as consequence of a higher environmental offer of medicinal plants and the prevalence of cultural elements of native peoples; in contrast, the construction of homegardens within a pluricultural context in urban areas promotes the incorporation of alien species in the local herbalist. Finally, we emphasize the possibility of integrating the official medicinal system with the traditional medicinal systems based in plants, contributing to the programs of conservation of biocultural heritage and primary health care as posed by the World Health Organization in its Traditional Medicine Strategy 20142023.